Effects of human factor on requirement volatility measures for efficient software requirement engineering - Askarinejadamiri, Zahra (2016)
Software is developed based on the requirements of users which are obtained during the requirements gathering activity in the requirement engineering process in software development projects. The aim is to collect complete and unambiguous requirements. Nevertheless, not all projects are free from requirement changes or requirements volatility which involves additions, deletions, and modifications of requirements. Frequent changes to requirements are a risk factor in software development projects. Moreover, software is developed based on human activities such as problem solving, analytical thinking, communication and cognitive reasoning. Although technical skill is important to a software project’s successful outcome, the human factor is a determining issue that affects most software projects. Thus, human factors are among the main challenges in requirements engineering including requirements volatility. Human as main part for software requirements gathering have an important role on requirements volatility. Changes in software requirements occur through the role of human in requirements gathering. However studies on human factors in requirements volatility are still lacking. Most of the studies have addressed the technical aspects of requirements gathering and requirements volatility in relation to productivity, software defects, and software release. A few studies focus on the factors that influence requirements volatility involving communication between users and developers, and defined the methodology for requirements analysis and modelling. Despite the maturity of human factors in many contexts, very little published literature discusses about human factors and requirements volatility. In this research, a human factors model on requirements volatility named as HF-RV model, is proposed. The constructs of the human factors model are human errors, moral capital, spiritual capital, human capital and human ability. The human factors model is derived from analysis of related literature in human factors theories which include personality theories and human errors theories. The model then had undergone further investigation to identify the relationships between human factors and requirements volatility by surveying two hundred fifteen experienced participants in requirements gathering. The data collected from the survey was analysed using SPSS and AMOS for structural equation modelling and other analysis. The results indicated considerable confirmatory for hypothesized model. Furthermore, Exploratory Factor Analysis, Confirmatory Factor Analysis, test for reliability and validity, and model fit test conducted show the model is acceptable. To gain more insight on usefulness of the model, opinion from experts were gathered through interview sessions. The results from this research reveal the significant impact of human error, moral capital, human capital and human ability on requirements volatility. However, spiritual capital impact on requirements volatility is statistically rejected. In short, it provides new insight into impact of human factors on requirements volatility in requirements gathering.